STRATEGI PEMBERIAN PAKAN YANG BERBEDA TERHADAP PERTUMBUHAN DAN KELANGSUNGAN HIDUP BENIH IKAN MAS (Cyprinus carpio) - Muhtadin muhtaddin; Fia Sri Mumpuni; Eko Rini Farastuti (Universitas Djuanda, 2023)
Goldfish is one type of freshwater fish that is quite popular with the public. This study aims to determine the absolute length growth, absolute weight growth and feed efficiency of carp (Cyprinus carpio) fry. This research was conducted on 26 July – 04 November 2022 at the Curug Barang Freshwater Seed Center. This study used a completely randomized design (CRD) with 4 treatments and 4 replications. The treatments used were: artificial feeding (A), Daphnia sp feeding (B), Tubipex sp 50% + Daphnia sp 50% combination feeding (C), and Tubipex sp feeding (D). Seed maintenance was carried out for 30 days. During rearing, fish were fed 3 times a day at 08.00, 13.00 and 18.00 WIB. Observation of absolute length, absolute weight, is done every 10 days. The growth in absolute length of carp seeds reared with different types of feed showed significantly different results (P<0.05). The highest absolute length was in the Tubifex sp (D) treatment, which was 1.86 cm and the lowest was in the artificial feed treatment (A), which was 0.78 cm. The absolute weight growth of carp seeds reared by giving different types of feed showed significantly different results (P<0.05). The highest absolute weight growth was found in the Tubifex sp (D) treatment, namely 2.45 grams. The most effective feed efficiency during fish rearing for 30 days was in the feed treatment Tubifex sp (D) with a value of 97.97% and the lowest was in the artificial feed treatment (A) with a value of 72.90%. The survival rate ranges from 99.16 - 99.25%. The survival rates for the Dhapnia sp (B), Dhapnia sp + Tubifex sp (C), Tubifex sp (D) treatments showed significantly different results (P<0.05).